Intranasal Delivery of Genistein-Loaded Nanoparticles as a Potential Preventive System against Neurodegenerative Disorders - Giovanna Rassu; Elena Piera Porcu; Silvia Fancello; Antonella Obinu; Nina Senes; Grazia Galleri; Rossana Migheli; Elisabetta Gavini; Paolo Giunchedi (MDPI AG, 2018)
Genistein has been reported to have antioxidant and neuroprotective activity. Despite encouraging in vitro and in vivo results, several disadvantages such as poor water solubility, rapid metabolism, and low oral bioavailability limit the clinical application of genistein. The aim of this study was to design and characterize genistein-loaded chitosan nanoparticles for intranasal drug delivery, prepared by the ionic gelation technique by using sodium hexametaphosphate. Nanoparticles were characterized in vitro and their cytotoxicity was tested on PC12 cells. Genistein-loaded nanoparticles were prepared, and sodium hexametaphosphate was used as a valid alternative to well-known cross-linkers. Nanoparticle characteristics as well as their physical stability were affected by formulation composition and manufacturing. Small (mean diameters of 200–300 nm) and homogeneous nanoparticles were obtained and were able to improve genistein penetration through the nasal mucosa as compared to pure genistein. Nanoparticle dispersions showed a pH consistent with the nasal fluid and preserved PC12 cell vitality.